Role of Clofazimine in Treatment of Mycobacterium avium Complex - Nasiri, Mohammad Javad; Calcagno, Tess; Hosseini, Sareh Sadat; Hematian, Ali; Nojookambari, Neda Yousefi; Karimi-Yazdi, Mohammadmahdi; Mirsaeidi, Mehdi (Frontiers in Medicine, 2021)
(1) Background: Nontuberculous mycobacteria (NTM), specifically Mycobacterium avium complex (MAC), is an increasingly prevalent cause of pulmonary dysfunction. Clofazimine has been shown to be effective for the treatment of Mycobacterium avium complex, but there were no published large-scale analyses comparing clofazimine to non-clofazimine regimens in MAC treatment. The objective of this large-scale meta-analysis was to evaluate patient characteristics and treatment outcomes of individuals diagnosed with MAC and treated with a clofazimine-based regimen. (2) Methods: We used Pubmed/Medline, Embase, Web of Science, and the Cochrane Library and searched for studies published January 1, 1990 to February 9, 2020. Two reviewers (SSH and NY) extracted the data from all eligible studies and differences were resolved by consensus. Statistical analyses were performed with STATA (version 14, IC; Stata Corporation, College Station, TX, USA). (3) Results: The pooled success treatment rate with 95% confidence intervals (CI) was assessed using random effect model. (4) Conclusions: The estimated pooled treatment success rates were 56.8% in clofazimine and 67.9% in non-clofazimine groups. Notably, success rates were higher (58.7%) in treatment of HIV patients with disseminated infection.